Recent status and trends of nanotechnology in cervical cancer: a systematic review and bibliometric analysis - Song, Xiangzhi; Li, Xun; Tan, Zhiwei; Zhang, Lushun (Frontiers in Oncology, 2024)
Cervical cancer is currently the second leading cause of death among women.However, there is a lack of effective treatment methods, and the existing treatments often result in significant adverse reactions and high chances of recurrence, which ultimately impact the prognosis of patients. As a result, the application of nanotechnology, specifically nanoparticle-based approaches, in the diagnosis and treatment of cervical cancer has gained significant attention. This study aims to examine the current research status and future development trends of nanotechnology in relation to cervical cancer using a bibliometric perspective.A bibliometric analysis was performed to gather relevant research papers from the Web of Science database. VOSviewer and CiteSpace were utilized to conduct quantitative analysis and identify hot topics in the field, focusing on countries, institutions, journals, authors, and keywords.Result: A total of 997 eligible literature were retrieved. From January 1, 2014 to September 20, 2023, the overall number of publications showed an upward trend. The paper mainly comes from China (n=414). The main institution is the Chinese Academy of Sciences (n=62), and 50% of the top 10 institutions in the number of documents issued are from China. First authors Ma, Rong (n=12) and Alifu, Nuernisha (n=12). The journal with the highest publication volume is ACS Applied Materials&INTERFACES (n=35), and the journal with the highest citation frequency is BIOMATERIALS (n=508). "Nanoparticles (n=296)", "cervical cancer (n=248)", and "drug delivery (n=218)" are the top three most frequently occurring keywords. In recent years, photothermal therapy and indocyanine green have become research hotspots. The application of nanotechnology in the field of cervical cancer has garnered considerable attention. Nanoparticles-based methods for diagnosis, administration, and treatment have proven to be instrumental in enhancing the sensitivity of cervical cancer detection, improving the accuracy and efficiency of administration, and reducing drug toxicity. Enhancing treatment efficacy and improving patient prognosis have emerged as current research priorities and future directions.